Drug-Resistant E. coli Causing UTI and Its Homoeopathic Management: Two Evidence-Based Case Reports - Ponnam, Hima Bindu; Jagadabhi, Santosh Kumar (Homœopathic Links, 2022)
Background Urinary tract infections (UTIs) comprise a troublesome array of symptomatology accounting for disruption in the quality of life of an individual to a significant extent. Increasing prevalence of the drug-resistant microbes in UTIs poses a major concern for treatment to the medical fraternity. Homoeopathy offers a safe and effective treatment option for treating a broad spectrum of multidrug-resistant diseases.Patient Profile Two patients presented with acute UTI for homoeopathic consultation. The conventional treatment options taken with rigorous antibiotic medications could not stop the frequent relapses and prolonged suffering. Indicated homoeopathic medicine was prescribed for the cases based on the characteristic symptoms. The improvement was assessed symptomatically and by urine culture reports. The outcome has been further verified through outcome in relation to impact on daily living (ORIDL).Result Homoeopathic medicine showed marked improvement in both cases by not only alleviating the symptoms of infection subjectively but also resolving the Escherichia coli (E. coli) bacterial infection confirmed through objective evidence of urine culture report.Conclusion Homoeopathic medicine found to be effective in relieving the acute UTI caused by antibiotic-resistant E. coli.
Keywords: UTI; homoeopathy; keynote prescription; centesimal potency; case reports; drug-resistant E. coli; evidence-based medicine